2019
DOI: 10.1177/2471549218821181
|View full text |Cite
|
Sign up to set email alerts
|

Topical and Intravenous Tranexamic Acid Are Equivalent in Decreasing Blood Loss in Total Shoulder Arthroplasty

Abstract: Introduction: Tranexamic acid (TXA) has been shown to be an effective modality to decrease blood loss in total shoulder arthroplasty (TSA). However, the most effective method of TXA administration remains controversial. The purpose of this study was to directly compare the use intravenous and topical TXA to determine which regimen was more effective in improving postoperative hemoglobin (Hb), transfusion rates, and patient outcomes after primary TSA. Methods: We conducted a retrospective review of 3 sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Of these 14 studies that used an IV approach, 10 reported favorable outcomes for postoperative hematologic parameters. The most commonly reported changes were a reduction in blood volume loss, reduction in hemoglobin or hematocrit change, and decreased drain output 1524 . Only 1 study, conducted by Kissin et al 25 , reported a negative finding in regard to blood volume loss with administration of IV TXA.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 14 studies that used an IV approach, 10 reported favorable outcomes for postoperative hematologic parameters. The most commonly reported changes were a reduction in blood volume loss, reduction in hemoglobin or hematocrit change, and decreased drain output 1524 . Only 1 study, conducted by Kissin et al 25 , reported a negative finding in regard to blood volume loss with administration of IV TXA.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there have not been many studies comparing these two methods of TXA application. Budge et al in 2019 conducted a retrospective review on a group of only three patients comparing whether Intravenous and topical TXA are equivalent in improving postoperative hemoglobin in TSA [ 33 ]. However, Li et al, in a meta-analysis, evaluated the efficiency and safety of combined use of intravenous and topical versus single intravenous TXA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion requirements were reported in all nine TSR studies [33][34][35][36][37][38][39][40]. RCT data showed a decrease in the number of blood transfusions in the TXA group compared with the placebo group (RR = 0.50; 95% CI: 0.16, 1.54; p = 0.919; Figure 5 top), but this was not significant.…”
Section: Transfusion Requirementsmentioning
confidence: 96%
“…Fifteen papers failed to meet the eligibility criteria. Therefore, nine studies were deemed eligible for inclusion in this systematic review and meta-analysis [33][34][35][36][37][38][39][40][41]. A PRISMA flow chart is provided in Figure 1.…”
Section: 1study Selectionmentioning
confidence: 99%